REAKSI ADAT KURANGNYA PERLENGKAPAN UPACARA PERKAWINAN PADA MASYARAKAT DAYAK KANAYAN DI DESA TELUK BAKUNG KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - NIM. A1011151151, SYARIFAH MELINDA (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac In practice, in the Dayak Kanayatn Tribe community in Teluk Village. In practice in the Kanayatn Dayak Tribe community in Teluk Bakung Village, Sungai Ambawang District, Kubu Raya Regency, there are also people who only carry out marriages using traditional methods and when carrying out traditional marriage ceremonies they ask for certain equipment. must be complete for the traditional marriage ceremony according to the applicable customs, and if they do not have incomplete wedding equipment, then the traditional leader cancels the traditional marriage ceremony. The equipment for the traditional marriage ceremony must be complete. For example, equipment brought by men to give to women are rings, women's clothing items such as jomuh (sarong) and bojuh (shirt), decorative equipment (powder, lipstick and comb), toiletries (soap, shampoo, toothpaste, toothbrush) and palm wine (a drink made from glutinous rice).Based on the background, the problem in this research can be formulated as